2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Income Tax Withholding for Farm Workers [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
Income tax withholding for farm workers means to withhold federal income taxes on the cash wages of farmworkers. This is EDIS document FE403, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.